Enterprise Information Systems : 21st International Conference, ICEIS 2019, Heraklion, Crete, Greece, May 3–5, 2019, Revised Selected Papers /: 21st International Conference, ICEIS 2019, Heraklion, Crete, Greece, May 3–5, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available